Metabolism of 2-acetylaminofluorene and benzo(a)pyrene and activation of food-derived heterocyclic amine mutagens by human cytochromes P-450 - MCMANUS, M. E; BURGESS, W. M; VERONESE, M. E; HUGGETT, A; QUATTROCHI, L. C; TUKEY, R. H (Cancer research (Chicago, Ill.), 1990)
The human P-450 CYP1A1 gene and a P450IA2 complementary DNA have been expressed in Cos-1 cells and the expressed proteins were assayed for their capacity to metabolize the carcinogens 2-acetylaminofluorene (AAF), benzo(a)pyrene, 2-amino-3-methylimidazo[4,5-f]quinoline (IQ), 2-amino-3,4-dimethylimidazo[4,5-f]quinoline, 2-amino-3,8-dimethylimidazo[4,5-f]quinoxaline, 2-amino-3,4,8-trimethylimidazo[4,5-f]quinoxaline, 2-amino-1-methyl-6-phenylimidazo[4,5-b]pyridine (PhIP) was determined. The expressed human P450IA1 and P450IA2 proteins, when run on a 7.5% sodium dodecyl sulfate-polyacrylamide gel, migrated with different mobilities, with the former displaying the lower molecular weight. In human liver microsomes from 18 subjects, only a protein band corresponding to P450IA2 was detectable. Cos-1 cell-expressed P450IA1 and P450IA2 were capable of N-hydroxylating AAF and these activities were inhibited by alpha-naphthoflavone. In human liver microsomes, a correlation of r = 0.76 (P less than 0.05; n = 18) was obtained between AAF N-hydroxylase activity and P450IA2 content. AAF N-hydroxylase activity of human liver microsomes was also strongly inhibited by alpha-naphthoflavone. Except in the case of PhIP, where both proteins exhibited similar activities, P450IA2 was at least an order of magnitude more efficient than P450IA1 in activating IQ, 2-amino-3,4-dimethylimidazo[4,5-f]quinoline, 2-amino-3,8-dimethylimidazo[4,5-f]quinoxaline, and 2-amino-3,4,8-trimethylimidazo[4,5-f]quinoxaline to mutagens as measured in the Ames test. Statistically significant correlations were obtained between IQ activation and P450IA2 content (r = 0.75, r2 = 0.56) and PhIP activation and P450IA2 content (r = 0.71, r2 = 0.5) in human liver microsomes. The activation of both IQ and PhIP by expressed proteins and human liver microsomes was strongly inhibited by alpha-naphthoflavone. The above data suggest a major role for P450IA2 in activation (N-hydroxylation) of aromatic amides and amines in human liver. When benzo(a)pyrene hydroxylase activity was determined, only Cos-1 cell-expressed P450IA1 exhibited appreciable activity. While alpha-naphthoflavone inhibited Cos-1 cell-expressed P450IA1 benzo(a)pyrene hydroxylase activity, it caused a marked stimulation of this activity in human liver microsomes, which lack P450IA1 protein. The lack of a role for P450IA proteins in benzo(a)pyrene metabolism is further supported by the poor correlation (r = 0.43, P greater than 0.05) between this activity and P450IA2 content of human liver microsomes. However, when P450IIIA3 content of the above human liver microsomes was determined by using the Western blot technique and correlated with benzo(a)pyrene metabolism, an r value of 0.70 (P less than 0.5) was obtained. These data suggest that human P450IIIA proteins are involved in benzo(a)pyrene metabolism.